Isolation and screening of heterocystous cyanobacterial strains for biodiesel production by evaluating the fuel properties from fatty acid methyl ester (FAME) profiles. (May 2015) - Anahas, Antonyraj Matharasi Perianaika; Muralitharan, Gangatharan
Highlights: Eleven heterocystous cyanobacterial strains were screened for biodiesel production. Biomass and lipid productivity along with the lipid content were examined. Biodiesel quality parameters were evaluated from FAME profiles. The best strain was selected using PROMETHEE-GAIA algorithm. Anabeana sphaerica MBDU105 is selected as the best strain for biodiesel production. Abstract: This study reports on the biodiesel quality parameters of eleven heterocystous cyanobacterial strains based on fatty acid methyl esters (FAME) profiles. The biomass productivity of the tested cyanobacterial strains ranged from 9.33 to 20.67 mg L −1  d −1 while the lipid productivity varied between 0.65 and 2.358 mg L −1  d −1 . The highest biomass and lipid productivity was observed for Calothrix sp. MBDU 013 but its lipid content is only 11.221 in terms of percent dry weight, next to the Anabaena sphaerica MBDU 105, whose lipid content is high. To identify the most competent isolate, a multi-criteria decision analyses (MCDA) was performed by including the key chemical and physical parameters of biodiesel calculated from FAME profiles. The isolate A. sphaerica MBDU 105 is the most promising biodiesel feed stock based on decision vector through Preference Ranking Organisation Method for Enrichment Evaluation (PROMETHEE) and Graphical Analysis for Interactive Assistance (GAIA) analysis.